Correlation Analysis Between Magnetic Resonance Imaging-Based Anatomical Assessment and Behavioral Outcome in a Rat Contusion Model of Chronic Thoracic Spinal Cord Injury - Xing, Cong; Jia, Zeyu; Qu, Haodong; Liu, Song; Jiang, Wang; Zhong, Hao; Zhou, Mi; Zhu, Shibo; Ning, Guangzhi; Feng, Shiqing (Frontiers in Neuroscience, 2022)
Although plenty of evidences from preclinical studies have led to potential treatments for patients with spinal cord injury (SCI), the failure to translate promising preclinical findings into clinical advances has long puzzled researchers. Thus, a more reliable combination of anatomical assessment and behavioral testing is urgently needed to improve the translational worth of preclinical studies. To address this issue, the present study was designed to relate magnetic resonance imaging (MRI) based anatomical assessment to behavioral outcome in a rat contusion model. Rats underwent contusion with three different heights to simulate various severities of SCI and their locomotive functions were evaluated by grid-walking test, Louisville swim scale (LSS), especially catwalk gait analysis system and basic testing Basso, Beattie, Bresnahan (BBB) score. The results showed that lesion area (LA) is a better indicator for damage assessment compared with other parameters in sagittal T2 weighted MRI (T2WI). Although two samples are marked as outliers by the box plot analysis, LA correlated closely with all of the behavioral testing without ceiling effect and floor effect. Moreover, with a moderate severity of SCI in a contusion height of 25mm, the smaller LA of spinal cord measured on sagittal T2WI correspond to the better functional performance, the smaller cavity region and glia scar, the more spared myelin, the higher volatility and the thicker bladder wall. We found that LA significantly related with behavior outcomes, which indicated that LA could be a proxy of damage assessment. The combination of sagittal T2WI and four types of behavioral testing can be used as a reliable scheme to evaluate the prognosis for preclinical studies of SCI.